The Relationship Between Dietary Patterns, Lifestyle, and Stress Levels with Dyspepsia Recurrence at Dalu X Public Health Center, Tanjung Morawa - Kristina Dameria Panggabean (Universitas Methodist Indonesia, 2025)
Background : Dyspepsia can be caused by eating and drinking habits suchas spicy food, excessive acidity or consumption of alcoholic drinks,carbonated and caffeinated drinks such as coffee, smoking, stress,Helicobacter Pylori infection, use of drugs and a history of disease (gastritis and gastric ulcers) which have an impact as risk factors fordyspepsia.Objective : to determine the relationship between diet, lifestyle and stresslevels on the recurrence of dyspepsia at the Dalu ResearchMethod : This research is an observational analytical research. Theresearch will be carried out in Jully of 2024. The research was carried outat the DaluConclusion : The number of respondents' eating patterns at the Dalu Thenumber of respondents' lifestyle at the Dalu X Tanjung MorawaCommunity Health Center was in the good category (84.3%). The totalstress level of respondents at the Dalu X Tanjung Morawa Health Centerwas in the medium category (47.1%). The number of recurrences ofdyspepsia at the Dalu X Tanjung Morawa Health Center was in thedyspepsia category (52.9%). There was a relationship between diet andrecurrence of dyspepsia at the Dalu X Tanjung Morawa CommunityHealth Center (p=0.000). There was no relationship between lifestyle anddyspepsia recurrence at the Dalu X Tanjung Morawa Community HealthCenter (p=0.150). There was a relationship between stress levels anddyspepsia recurrence at the Dalu X Tanjung Morawa Community HealthCenter (p=0.000).Keywords : Diet, lifestyle, stress, dyspepsia